2015
DOI: 10.1016/j.immuni.2015.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Interleukin-2 Elicit Selective T Cell Subset Potentiation through Distinct Conformational Mechanisms

Abstract: SUMMARY Interleukin-2 (IL-2) is a pleiotropic cytokine that regulates immune cell homeostasis, and has been used to treat a range of disorders such as cancer and autoimmune disease. IL-2 signals via interleukin-2 receptor-β (IL-2Rβ):IL-2Rγ heterodimers on cells expressing high (regulatory T cells, Treg) or low (effector cells) amounts of IL-2Rα (CD25). When complexed with IL-2, certain anti-cytokine antibodies preferentially stimulate expansion of Treg (JES6-1) or effector (S4B6) cells, offering a strategy for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
235
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(249 citation statements)
references
References 45 publications
13
235
0
1
Order By: Relevance
“…These data would rather argue against IL-2R crosslinking by IL-2/ S4B6 complexes. For IL-2/JES6-1 complexes, STAT5 phosphorylation was reduced in CD25 + YT-1 human NK cells compared with IL-2 in vitro [13], although another report using in vitro stimulation of total mouse splenocytes suggested that, compared with IL-2, IL-2/JES6-1 complexes led to increased STAT5 phosphorylation in CD4 + T cells [71]. In line with the former Recent structural data not only provide evidence for the steric aspects of the abovementioned model but also suggest mild antagonistic and allosteric forces at work (Figure 3).…”
Section: Il-2/mab Complexesmentioning
confidence: 93%
See 3 more Smart Citations
“…These data would rather argue against IL-2R crosslinking by IL-2/ S4B6 complexes. For IL-2/JES6-1 complexes, STAT5 phosphorylation was reduced in CD25 + YT-1 human NK cells compared with IL-2 in vitro [13], although another report using in vitro stimulation of total mouse splenocytes suggested that, compared with IL-2, IL-2/JES6-1 complexes led to increased STAT5 phosphorylation in CD4 + T cells [71]. In line with the former Recent structural data not only provide evidence for the steric aspects of the abovementioned model but also suggest mild antagonistic and allosteric forces at work (Figure 3).…”
Section: Il-2/mab Complexesmentioning
confidence: 93%
“…phosphorylation [13] and lower proliferation of wild-type and CD25 À/À memory-phenotype mouse CD8 + T cells [9]. These data would rather argue against IL-2R crosslinking by IL-2/ S4B6 complexes.…”
Section: Il-2/mab Complexesmentioning
confidence: 98%
See 2 more Smart Citations
“…Une autre stratégie développée plus récemment chez la souris, a consisté à utiliser un anticorps dirigé contre l'IL-2 (le JES6-1) qui, par une conjonction d'effets stériques et allostériques, modifie la capacité de l'IL-2 à recruter ses chaînes réceptrices et lui confère une forte sélec-tivité pour les cellules exprimant la chaîne α [40,41]. L'intérêt de ces molécules a été validé chez la souris dans plusieurs modèles d'inflammation chronique ou de maladies auto-immunes [42].…”
Section: Summary Interleukin 2 Revival: a Revisited Model And New Theunclassified